Association between sensitivity to thyroid hormone indices and frailty in the elderly: a cross-sectional study - Qi, Xinyu; Fang, Jia; Zhang, Jiru; Chen, Jihai; Zhang, Daowen; Shi, Runqing; Zhang, Yusheng; Wei, Lijun; Yan, Lu; Sheng, Yunlu; Ding, Guoxian; Ouyang, Xiaojun; et al. (Frontiers in Endocrinology, 2025)
ObjectiveFrailty is a prevalent geriatric syndrome that affects several systems and lacks accurate evaluation indications. Previous studies on the association between thyroid function and frailty have contradicted. This study introduced the thyroid hormone sensitivity indices to analyze their connection with frailty and evaluate its usefulness in assessing frailty.MethodsA total of 1030 Chinese elderly individuals were included. The FRAIL scale was utilized to assess the frailty status of subjects. The thyroid hormone sensitivity indices, including the following: Thyrotrophic Thyroxine Resistance Index (TT4RI), Thyroid Stimulating Hormone Index (TSHI), Thyroid Feedback Quantile-based Index (TFQI) and Free Triiodothyronine/Free Thyroxine (FT3/FT4), were calculated based on thyroid function. A multivariate logistic regression analysis assessed the association between frailty and these markers.ResultsThe study findings indicated that frailty groups exhibited lower levels of FT3 and TSH compared to non-frailty groups. Additionally, the central sensitivity index of thyroid hormone [TFQI(FT3)] and the peripheral sensitivity index (FT3/FT4) were also lower in frailty groups. Following the adjustment for multiple variables, FT3 (OR=0.640, 95%CI: 0.534-0.768, p <0.001), TSHI (OR=0.829, 95%CI: 0.708-0.971, p =0.020), TFQI(FT3) (OR=0.358, 95%CI: 0.233-0.550, p <0.001) and FT3/FT4 (OR=0.006, 95%CI: 0.001-0.058, p <0.001) showed a negative connection with the score of FRAIL scale.ConclusionSerum FT3 and TSH declined in frail patients, whereas there was no alteration in serum FT4. Both the decrease of central sensitivity index of thyroid hormone, TSHI and TFQI(FT3), and peripheral sensitivity index, FT3/FT4, were associated with frailty assessed by FRAIL scale. Specific thyroid measures, especially FT3, TFQI(FT3) and FT3/FT4, would be served as easily measurable indications that are essential for evaluating frailty.